Contribution to the knowledge of Chinese Gryllacrididae II: Study of the genus of Microlarnaca (Orthoptera:) with description one new species from Yunnan, China - Lu, Xiangyi; Bin, Wei; Bian, Xun (Zootaxa, 2021)
One new species of Microlarnaca discovered by the authors’s group during expeditions to Yunnan Province is described: Microlarnaca zhengi Lu & Bian sp. nov.. Diagnostic note, images of the morphological characters and description of tegminal veins of Microlarnaca dicrana (Bey-Bienko, 1962) are also given.